1998
DOI: 10.1111/j.1600-0714.1998.tb01963.x
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial p53 gene expression and mutational analysis, combined with growth fraction assessment, in oral lichen planus

Abstract: The immunohistochemical detection of epithelial p53 protein expression in oral lichen planus (OLP) biopsies was supplemented with molecular analysis for mutations of the p53 gene using the polymerase chain reaction ‐ single stranded conformational polymorphism (PCR‐SSCP) technique. p53 protein expression, in the basal epithelial cell layer, as detected by the DO7 and 1801 antibodies, was significantly more frequent in OLP compared with other oral keratoses and normal mucosa, as was the growth fraction. The 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 39 publications
0
23
1
Order By: Relevance
“…The very few mutational analyses of the p53 gene in OLP have produced contradictory results. Whereas Ogmundsdottir et al (2002) observed mutation of this gene in 30% of OLP cases, Schifter et al (1998) detected no cases with this mutation. Our group (González‐Moles et al , 2006) and other authors (Dekker et al , 1997; Tanda et al , 2000) have proposed that the frequent overexpression of p53 largely corresponds to the wild type of the protein, which may act preferentially to halt the cell cycle for DNA repair.…”
Section: Possible Molecular Bases For An Epithelium Prone To Malignanmentioning
confidence: 93%
See 2 more Smart Citations
“…The very few mutational analyses of the p53 gene in OLP have produced contradictory results. Whereas Ogmundsdottir et al (2002) observed mutation of this gene in 30% of OLP cases, Schifter et al (1998) detected no cases with this mutation. Our group (González‐Moles et al , 2006) and other authors (Dekker et al , 1997; Tanda et al , 2000) have proposed that the frequent overexpression of p53 largely corresponds to the wild type of the protein, which may act preferentially to halt the cell cycle for DNA repair.…”
Section: Possible Molecular Bases For An Epithelium Prone To Malignanmentioning
confidence: 93%
“…Most studies on cell proliferation in OLP have reported a marked increase in the proliferation rate of basal epithelial cells (Maidhof et al , 1981; Schifter et al , 1998; da Silva Fonseca and do Carmo, 2001; Valente et al , 2001; Taniguchi et al , 2002; González‐Moles et al , 2006), and some authors have proposed that this might be an important event in the development of cancer in OLP (Taniguchi et al , 2002). Valente et al (2001) found that the cell proliferation rate, according to the ki‐67 expression, was significantly higher in OLP patients who developed cancer than in patients who did not.…”
Section: Possible Molecular Bases For An Epithelium Prone To Malignanmentioning
confidence: 99%
See 1 more Smart Citation
“…Exons 5 to 9 of p53 were initially amplified in all samples using the primers and cycling parameters described. 23,24 Negative controls without DNA were included in each PCR cycle. PCR cycles were performed in a Hybaid Px2 thermal cycler.…”
Section: Dna Extraction and Pcrmentioning
confidence: 99%
“…According to these studies, the proliferative activity of most epithelial cells is increased in OLP. Van Oijen et al suggest that cyclin D1, which is considered to be a cell growth stimulation factor, may overcome the inhibitory effect exerted by p21 in the oral mucosa 31 …”
Section: Discussionmentioning
confidence: 99%